Clinical efficacy of tacrolimus in systemic lupus erythematosus with various manifestations: a real-world study - Bai, Wei; Li, Mengtao; Zhou, Shuang; Peng, Liying; Zhao, Jiuliang; Tian, Xinping; Wang, Qian; Leng, Xiaomei; Zhang, Shangzhu; Wang, Yanhong; Zhao, Yan; Zeng, Xiaofeng (Chinese medical journal, 2022)
Based on the Chinese SLE Treatment and Research group registry,[3] SLE patients who fulfill the 2012 Systemic Lupus International Collaborating Clinics classification criteria and with a Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) ≥2 were included from March 2016 to March 2020 in Peking Union Medical College Hospital. According to the European consensus criteria, SLE remission was defined as a clinical SLEDAI-2K = 0 and PGA <0.5, with prednisolone (or equivalent) ≤5 mg daily. Pulmonary arterial hypertension (PAH) was defined as a resting mean pulmonary artery pressure >25 mmHg assessed by right heart catheterization, in the presence of normal pulmonary capillary wedge pressure <15 mmHg and pulmonary vascular resistance >3 Wood units, or a resting systolic pulmonary artery pressure >40 mmHg estimated by transthoracic echocardiography. According to our study, tacrolimus combined with or without vasodilator therapy might improve not only the SLEDAI-2K score but also the heart function of patients with SLE-PAH.